The Effect of Brand Awareness and Service Quality on Customer Satisfaction and Its Implications for Container Terminal Customer Loyalty - Utomo, Satyo; Saragih, Ardian (International Journal of Advanced Multidisciplinary, 2023)
The purpose of this study was to determine the effect of brand awareness and service quality on customer satisfaction and the implications for customer loyalty in container terminals. Object research in Port of Tanjung Priok, PT. Jakarta International Container Terminal (JICT). This study uses quantitative research, with a sample size of 150 respondents from 500 population. Data collection techniques using questionnaires and data analysis using path analysis. The results of this study indicate: There is a significant positive (unidirectional) effect of Brand Awareness on Customer Satisfaction when T-Statistics value (3.171) > T table value (1.976) and P-value (0.002) <0.05, next there is a significant positive (unidirectional) effect of Brand Awareness on Consumer Loyalty when T-Statistics value (6.185) > T table value (1.976) and P-value (0.000) <0.05, then our research finding significant positive (unidirectional) effect of Service Quality on Customer Satisfaction when T-Statistics value (4.512) > T table value (1.976) and P-value (0.000) <0.05. There is a significant positive (unidirectional) effect of Service Quality on Consumer Loyalty when T-Statistics value (5.494) > T table value (1.976) and P-value (0.000) <0.05. For the last there is a significant positive (unidirectional) effect of Consumer Loyalty on Customer Satisfaction when T-Statistics value (4.895) > T table value (1.976) and P-value (0.000) <0.05. Based on the results of this study, it was found that brand awareness is very influential. Hence, container terminal management in the future can continue to improve branding-based business models that create the ability for them to win the competition.